Aplicação da NR-18 em canteiro de obra: estudo de caso em Tibau/RN - Brito, Felipe Eduardo Sá de (Universidade Federal Rural do Semi-Árido, 2018)
The civil construction sector in Brazil still plays an important role in the national economy, being one of the largest generators of employment. When the execution of a work begins, the first activity to be developed is the implantation of the construction site. Construction sites are often questioned regarding their organization and formatting. Construction site planning is an important activity and precedes the beginning of a work, the main planning function of the site is the best arrangement of available physical space. The bed can be classified as wide and its layout can be considered as being fixed. In the design of the design of the layout was taken into account factors of integration, minimum distance and obedience to the flow of operations. This study has the purpose of analyzing a construction site in operation, identifying its critical points and representing the layout of the current site, as well as representing the ideal layout according to the NR-18. Two types of research were adopted for the conception of this work: both the bibliographic research and the case study were carried out. It was evident the lack of planning of the company regarding the beginning of the work, not meeting the norms in force for a good execution of the same. The bed is installed on a very wide ground with many spaces available, which increases the possibility of greater disorganization in the arrangement of the space when one does not have the due initial study for implantation of the layout.
Monografia
Keywords: Layout; Engenharia civil; Planejamento; Layout; Civil engineering; Planning; ENGENHARIAS::ENGENHARIA CIVIL